Measuring Cumulative Stressfulness: Psychometric Properties of the COVID-19 Stressors Scale. (February 2021) - Tambling, Rachel R.; Russell, Beth S.; Park, Crystal L.; Fendrich, Michael; Hutchinson, Morica; Horton, Abagail L.; Tomkunas, Alexandria J.
Scales assessing stressor exposure often fail to demonstrate adequate psychometric qualities, demonstrating low interitem reliability or complex factor structures, as would be expected, given that the majority of stressors are independent events. However, in large-scale mass crisis events, the stressors may be highly interrelated, indicating shared experience. Furthermore, few stressor exposure scales also measure appraised stressfulness of those stressors. Development of a psychometrically sound measure of both stressor exposure and appraisal advances the study of highly stressful events such as community-wide crises, especially in providing a useful measure of its cumulative stressfulness. The coronavirus disease 2019 (COVID-19) pandemic is an enduring, worldwide stressor with an indefinite timeline. The COVID-19 Stressor Scale is a 23-item measure of stressor exposure and appraisal related to the pandemic developed within the first weeks of widespread shelter-in-place practices in the Unites States. We present initial psychometric results of the COVID-19 Stressor Scale. Results of a principal components analysis indicate that the measure is unidimensional and has strong internal consistency. Evidence of convergent and discriminant validity were demonstrated. The COVID-19 Stressor Scale is a useful measure for studying the ongoing stressors associated with the pandemic and presents a model for measuring other massive, ongoing crises.